Gender differences in game responses during badminton match play - Fernandez-Fernandez, J.; de la Aleja Tellez, J. G.; Moya-Ramon, M.; Cabello-Manrique, D.; Mendez-Villanueva, A. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to evaluate possible gender differences in match play activity pattern [rally duration, rest time between rallies, effective playing time, and strokes performed during a rally] and exercise intensity (heart rate [HR], blood lactate [La], and subjective ratings of perceived exertion [RPE]) during 9 simulated badminton matches in male (n = 8) and female (n = 8) elite junior (16.0 ± 1.4 years) players. Results showed significant differences (all p < 0.05; effect size (ES) = 0.80-1.56) between male and female players in the activity pattern of match play, with male players engaged in longer rallies (6.8 ± 4.8 vs. 5.7 ± 3.1 seconds), executing more strokes per rally (6.4 ± 4.8 vs. 4.7 ± 2.8) and resting more between rallies (10.5 ± 8.8 vs. 8.8 ± 7.2 seconds) than female players. No clear differences (all p > 0.05; ES = -0.33 to 0.08) were observed between female or male players in average HR (174 ± 7 vs. 170 ± 9 b/min), %HRmax (89.2 ± 4.0% vs. 85.9 ± 4.3%), La (2.5 ± 1.3 vs. 3.2 ± 1.8 mmol/L), and RPE values (14.2 ± 1.9 vs. 14.6 ± 1.8) during match play, although male players spent more time (moderate effect sizes) at intensities between 81 and 90% HRmax (35.3 ± 17.9 vs. 25.3 ± 13.6; p < 0.05; ES = 0.64) in the second game. There seemed to be a trend toward an increased playing intensity (i.e., higher HR, La, and RPE) from the first to the second game, highlighting the higher exercise intensity experienced during the last part of the match. The clear between-gender differences in activity patterns induced only slightly different physiological responses.